(untitled) (Research, Society and Development, 2026)
This study aimed to extract bioactive compounds, develop, and evaluate the stability, sensory performance, and therapeutic efficacy of a pomegranate-extract dermocosmetic for complementary rheumatoid arthritis (RA) treatment. This applied experimental research involved extract production followed by phytochemical screening to identify bioactive compounds. Pre-formulation studies, bench-scale development, labeling, microbiological assays, and stability tests (preliminary, accelerated, and long-term) were performed. Finally, twenty volunteers used the product and completed a sensory and therapeutic evaluation questionnaire. Extract testing yielded satisfactory results, confirming secondary metabolites with anti-inflammatory, antioxidant, and antimicrobial properties. The emulsion showed excellent performance, and the final formulation maintained stability throughout all tests, with no statistically significant changes over 70 days. No microbial contamination was detected, and acceptability rates exceeded 90% across all evaluated attributes. Furthermore, participants reported a reduction in pain and joint stiffness, alongside improved quality of life. The pomegranate cream demonstrated stability, safety, and excellent sensory acceptability. Future studies should extend the stability and clinical evaluation periods to further validate these benefits.